Mitochondrial might: powering the peripartum for risk and resilience - Gorman-Sandler, Erin; Wood, Gabrielle; Cloude, Nazharee; Frambes, Noelle; Brennen, Hannah; Robertson, Breanna; Hollis, Fiona (Frontiers in Behavioral Neuroscience, 2023)
The peripartum period, characterized by dynamic hormonal shifts and physiological adaptations, has been recognized as a potentially vulnerable period for the development of mood disorders such as postpartum depression (PPD). Stress is a well-established risk factor for developing PPD and is known to modulate mitochondrial function. While primarily known for their role in energy production, mitochondria also influence processes such as stress regulation, steroid hormone synthesis, glucocorticoid response, GABA metabolism, and immune modulation--all of which are crucial for healthy pregnancy and relevant to PPD pathology. While mitochondrial function has been implicated in other psychiatric illnesses, its role in peripartum stress and mental health remains largely unexplored, especially in relation to the brain. In this review, we first provide an overview of mitochondrial involvement in processes implicated in peripartum mood disorders, underscoring their potential role in mediating pathology. We then discuss clinical and preclinical studies of mitochondria in the context of peripartum stress and mental health, emphasizing the need for better understanding of this relationship. Finally, we propose mitochondria as biological mediators of resilience to peripartum mood disorders.